'Knowledge for better health' revisited - the increasing significance of health research systems: a review by departing Editors-in-Chief - Stephen R. Hanney; Miguel A. González-Block (BMC, 2017)
Abstract How can nations organise research investments to obtain the best bundle of knowledge and the maximum level of improved health, spread as equitably as possible? This question was the central focus of a major initiative from WHO led by Prof Tikki Pang, which resulted in a range of developments, including the publication of a conceptual framework for national health research systems - Knowledge for better health - in 2003, and in the founding of the journal Health Research Policy and Systems (HARPS). As Editors-in-Chief of the journal since 2006, we mark our retirement by tracking both the progress of the journal and the development of national health research systems. HARPS has maintained its focus on a range of central themes that are key components of a national health research system in any country. These include building capacity to conduct and use health research, identifying appropriate priorities, securing funds and allocating them accountably, producing scientifically valid research outputs, promoting the use of research in polices and practice in order to improve health, and monitoring and evaluating the health research system. Some of the themes covered in HARPS are now receiving increased attention and, for example, with the assessment of research impact and development of knowledge translation platforms, the journal has covered their progress throughout that expansion of interest. In addition, there is increasing recognition of new imperatives, including the importance of promoting gender equality in health research if benefits are to be maximised. In this Editorial, we outline some of the diverse and developing perspectives considered within each theme, as well as considering how they are held together by the growing desire to build effective health research systems in all countries. From 2003 until mid-June 2017, HARPS published 590 articles on the above and related themes, with authors being located in 76 countries. We present quantitative data tracing the journal's growth and the increasing external recognition of its role. We thank the many colleagues who have kindly contributed to the journal's success, and finish on an exciting note by welcoming the new Editors-in-Chief who will take HARPS forward.